2020
DOI: 10.2196/16921
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Patient Portals in Hospitals: Qualitative Study

Abstract: Background Theoretical models help to explain or predict the adoption of electronic health (eHealth) technology and illustrate the complexity of the adoption process. These models provide insights into general factors that influence the use of eHealth technology. However, they do not give hospitals much actionable knowledge on how to facilitate the adoption process. Objective Our study aims to provide insights into patient portal adoption processes amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Margolius et al [ 103 ] found that having a wealthier or larger patient population and working more days per week resulted in primary care physicians receiving more messages from patients, which the authors stratified into message types. Provider use has been shown to lead to patient use [ 20 ], but while patients can be led toward engagement with a system required by their physicians, they can also be led away from a system not utilized by their providers [ 104 ] (eg, if patients message their providers but don’t receive a response). As mentioned previously, patient portal utilization has been employed as a proxy for patient engagement, with increased portal usage associated with better patient outcomes [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Margolius et al [ 103 ] found that having a wealthier or larger patient population and working more days per week resulted in primary care physicians receiving more messages from patients, which the authors stratified into message types. Provider use has been shown to lead to patient use [ 20 ], but while patients can be led toward engagement with a system required by their physicians, they can also be led away from a system not utilized by their providers [ 104 ] (eg, if patients message their providers but don’t receive a response). As mentioned previously, patient portal utilization has been employed as a proxy for patient engagement, with increased portal usage associated with better patient outcomes [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lacking standardized definitions, variable consistency in the application of MU terminology appears throughout the published literature [ 2 , 32 , 43 , 106 ]. At the most fundamental level, the lack of distinction between the patient health record (PHR), whose ownership and management lies with the patient, and the patient portal, whose ownership and management lies with the health care organization, was evident in publications that investigated patient portals but included information on PHRs in the statistical analysis [ 13 , 104 , 107 ]. Further, Devkota and colleagues [ 51 ] highlighted that mixed outcomes regarding the relationship between frequency of portal utilization and health outcomes are rooted in how studies analyze portal interaction; while some studies focused on message counts [ 31 , 41 , 70 ], others focused on interaction intensity with providers through portal messaging, stratifying by no use, read-only, and read-and-write [ 18 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the increasing interest in patient portals, the volume of compelling studies in the field, sustained by the facts and figures, remains fairly limited [8]. Available studies typically address: technological development, adoption, and use of patient portals [9,10], electronic health records and other health documents available through patient portals [11,12], patient engagement and communication [13,14], eHealth literacy [15,16], as well as different medical conditions that can be managed through patient portals [17,18]. However, these studies touch upon one or more features of patient portals under normal circumstances, so their findings are only partially applicable in the present pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on patient portals are from the US, which means that there is less knowledge on patient portals in a European context [ 12 14 ]. Most studies are conducted within one healthcare domain [ 15 , 16 ] or on patient portals for specific conditions [ 17 , 18 ]. Although eHealth tools have been put forward as central for improving integrated care [ 19 , 20 ] few studies have focused on the processes of establishing a patient portal across healthcare domains [ 21 ].…”
Section: Introductionmentioning
confidence: 99%